Supine head tremor: a clinical comparison of essential tremor and spasmodic torticollis patients. Issue 2 (5th November 2011) - Agnew, Angus; Frucht, Steven J; Louis, Elan D
Abstract : Background: Essential tremor (ET) is among the most misdiagnosed neurological diseases, and overdiagnosis is especially common. As many as 30–50% of supposed 'ET' cases have other diagnoses, with dystonia prominent among these. Therefore, the recognition of differences in tremor phenomenology has potential diagnostic value for practising clinicians. There is an anecdotal sense that head tremor in ET is positional rather than resting, a feature which could aid in the diagnosis, yet no published data exist. Methods: In this cross-sectional study of ET and spasmodic torticollis (ST) patients (3:1 matching) who had head tremor while upright, the prevalence of supine (ie, resting) head tremor was compared. Results: There were 60 ET cases and 19 ST cases with head tremor while seated. When supine, head tremor persisted in only 5/60 (8.3%) ET versus 13/19 (68.4%) ST cases (p<0.001), indicating that essential head tremor is more likely to resolve in the supine position than is the head tremor of ST. Supine head tremor, when present in ET, did not seem to preferentially occur in patients with more severe disease (p>0.05). Conclusions: These results indicate that there is some validity to the anecdotal sense that head tremor in ET is a postural tremor that dissipates when a patient lies down; by contrast, in ST, head tremor more often persists. In a clinical context, these results have potential implications in diagnostically ambiguous patients with head tremor. Physicians should consider asking their tremor patients to lie down to assess whether head tremor resolves.